2016
DOI: 10.1177/1545968316644344
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Cervical Spinal Cord Networks to Reenable Volitional Control of Hand Function in Tetraplegic Patients

Abstract: Background Paralysis of the upper-limbs from spinal cord injury results in an enormous loss of independence in an individual’s daily life. Meaningful improvement in hand function is rare after one year of tetraparesis. Therapeutic developments that result in even modest gains in hand volitional function will significantly impact the quality of life for patients afflicted with high cervical injury. The ability to neuromodulate the lumbosacral spinal circuitry via epidural stimulation in regaining postural funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
126
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(134 citation statements)
references
References 35 publications
5
126
1
2
Order By: Relevance
“…This effect is evident in spinal motor evoked potentials of proximal and distal leg muscles to single stimulation pulses [23]. We have found that epidural SCS combined with training can increase hand grip force in spinal patients with cervical injuries [18]. This suggests that similar interventions of training and cervical TSCS could also benefit for children with CP.…”
Section: Discussionmentioning
confidence: 77%
“…This effect is evident in spinal motor evoked potentials of proximal and distal leg muscles to single stimulation pulses [23]. We have found that epidural SCS combined with training can increase hand grip force in spinal patients with cervical injuries [18]. This suggests that similar interventions of training and cervical TSCS could also benefit for children with CP.…”
Section: Discussionmentioning
confidence: 77%
“…Reported diameters for both axon types, including myelin, are within a range of 13 µm to 20 µm for afferent (Ia) fibers [46] and 16 µm to 20 µm for efferent axons originating from cortical Betz neurons [47,48]. The inner axonal diameter, without myelin, was estimated via multiplication of the g-ratio (g=0.6) [49], whereby the chosen axon diameter of 10 µm is within the resulting range for both axons.…”
Section: Finite Element Modelmentioning
confidence: 99%
“…For instance, whereas reducing spasticity may require the downregulation of the reflexive pathways, an increase in corticospinal connection strength is required when aiming to aid voluntary motor control. Further investigation in this direction could be performed by varying electric field amplitude and direction [10,11,49] in combination with pathway specific neural activity [10]. In parallel to that, screening for other, known genetic dependencies may additionally help to explain response differences across subjects [21].…”
Section: Clinical and Scientific Implicationsmentioning
confidence: 99%
See 2 more Smart Citations